PENGARUH KETERLIBATAN GURU-SISWA DALAM MENULIS KARANGAN EKSPOSISI MENGGUNAKAN MODEL EXPERIENTIAL LEARNING DI SMA NEGERI 2 INDRAMAYU - Logita, Embang; Triana Winata, Nana (Bahtera Indonesia, 2020)
In learning expositional text, there is material to identify, compile, analyze, and produce. Producing as a final project of learning exposition text because in producing students are able to think critically and student are considered to have mastered the material about identifiying, compiling and analyzing. Producing in exposition text materian in the form of writing. The use of models, methods and techniques in learnin exposition text is very important to help students more easily understand the subject conveyed by the teacher. The use of experiential learning in the learning process is an effort to develop and build student’klowlegde through their experiences. Teacher-student involvement through an experiential learning models based on student intelligence to improve skills in producing exposition text is a models that involves the active role of student by writing down their own ideas based on the experiences of student who vary according to their reseptive intellegences so that each student in producing exposition text will be varied so that this learning models is expected to help student develop or improve wrting skill especially in producing text. Keyword: exposition text, experiential learning, teacher-student involvement